Business Models and Sustainable Development Goals - Ensign, Prescott C. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue on "Business Models and Sustainable Development Goals (SDG)" presents five research studies that examine transformative business models designed to support the United Nations SDG Agenda for 2030. The studies examine SDGs from the firm to national levels. Every organization has a business model that defines how the organization is designed to function. It is the engine that powers an organization, defining the value proposition of the venture, how it balances resources with the ecosystem where it operates, and how it generates cash flow and creates value. Changes to an organization's business model are recognized as a fundamental approach to implementing innovations for sustainability. The capability to transform or transition to new business models is an important source of competitive advantage, providing leverage to improve the performance of an organization. A sustainable business model includes pro-active management, monetary and non-monetary value for a broad range of stakeholders, and takes a long-term perspective. A sustainable business model is where change, success, and hope for our planet's future rests.